Fish Boat Building as a Supporting Facility for Lobster Cultivation in Banyuwangi - Budianto Budianto; M. Basuki Rahmat; Yuning Widiarti; Imam Sutrisno (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The economic condition of the coastal communities of East Java, especially in Banyuwangi, is strongly influenced by the tourism and fishing sectors. This condition needs to be developed with supporting facilities such as the procurement of fishing vessels. Procurement of fishing vessels must be designed with a feasibility study on vessel operations. In general, coastal conditions have shallow water depths and are often used by coastal communities for lobster cultivation. The supporting fishing vessels must be able to maneuver properly and not damage the ecosystem so that the existence of coral reefs is maintained. The fishing boats that support lobster aquaculture are designed with good maneuverability by taking into account the speed, the result of the waves formed and the capacity of the ship. The results of the design of fishing boats supporting lobster cultivation obtained that the main size of the ship is 13.00 meters long, 3.00 meters wide and 0.8 meters draft with a speed of 12 knots, reaching a designed mileage of 30 km in shallow water operational conditions